PERANCANGAN SISTEM BACKUP DAYA DAN TELEMONITORING DATA DENGAN PROTOKOL MQTT PADA SMART INKUBATOR BAYI - Geraldio Ramadhan Safitri; n/a Rahmadwati; Moch. Rusli (Jurnal Mahasiswa TEUB, 2023)
Indonesia is ranked the fifth country with the world’s most preterm babies. Therefore, the demand for infant incubators remains high. However, most infant incubators today still have some drawbacks, namely, the incubator relies on a grid power source. If a power outage happens, the incubator cannot be used. This research aims to solve the issue by designing a backup system for the incubator integrated with the Internet of Things (IoT) concept. The proposed system consists of an Automatic Transfer Switch (ATS) system, an automatic charging system, and a telemetry unit that can transmit incubator status data to a mobile application via the MQTT protocol. The test result shows that the designed ATS system can switch sources with a delay of 1.085 seconds for the PLN grid – inverter and 0.245 seconds for the inverter – PLN grid. The automatic charging system successfully recharges the Valve Regulated Lead Acid (VRLA) battery using a 3-stage charging method. Furthermore, the designed system can send incubator status data via MQTT protocol to mobile applications with a delivery time of 0.110 seconds. The designed MQTT topology has high scalability proven by the test, that it can connect with up to 1000 clients on one topic. Index Terms—Infant Incubator, Backup Power System, MQTT DAFTAR PUSTAKA[1] World Health Organization, “Born too soon,” Neuroendocrinol. Lett., vol. 25, no. SUPPL. 1, pp. 133–136, 2012, doi: 10.2307/3965140.[2] M. Ali, M. Abdelwahab, S. Awadekreim, and S. Abdalla, “Development of a Monitoring and Control System of Infant Incubator,” 2018. doi: 10.1109/ICCCEEE.2018.8515785.[3] PT PLN (Persero), “PT PLN in Number 2021 (Statistik PLN 2021),” pp. 1–102, 2021, [Online]. Available: https://web.pln.co.id/statics/uploads/2022/08/StatistikPLN-2021-29-7-22-Final.pdf[4] V. Hall, E. Geise, and N. H. Kashou, “The IncuLight: Solar-powered infant incubator,” 2014. doi: 10.1109/GHTC.2014.6970285.[5] I. Roihan, K. Tjandaputra A., E. A. Setiawan, and R. A. Koestoer, “Installing and testing the grashof portable incubator powered using the solar box ‘becare’ for remote areas without electricity,” Evergreen, vol. 7, no. 4, 2020, doi: 10.5109/4150516.[6] M. Syahid, D. Irianto, E. Sunarno, and S. St, “Rancang Bangun Charger Baterai dan Automatic Transfer Switch ( ATS ) Panel Surya – PLN Untuk Sumber Daya Tempat Sampah Otomatis,” J. Elektro PENS, vol. 2, no. 2, 2014.[7] I. A. Lazuardi, I. W. Farid, and C. W. Priananda, “Automatic Transfer Switch Dilengkapi Fitur Monitoring Website pada On-Grid Solar Home System,” J. Tek. ITS, vol. 10, no. 2, 2021, doi: 10.12962/j23373539.v10i2.68713.[8] I. Sukma et al., “Real-time wireless temperature measurement system of infant incubator,” Int. J. Electr. Comput. Eng., vol. 13, no. 1, pp. 1152–1160, 2022, doi: 10.11591/ijece.v13i1.pp1152-1160.